RNA Methylation in Systemic Lupus Erythematosus - Lv, Xinyi; Liu, Xiaomin; Zhao, Ming; Wu, Haijing; Zhang, Wuiguang; Lu, Qianjin; Chen, Xiangmei (Frontiers in Cell and Developmental Biology, 2021)
Systemic lupus erythematosus is an autoimmune disease with complicated clinical manifestations. Although our understanding of the pathogenesis of SLE has greatly improved, understanding the pathogenic mechanisms of SLE is still limited by disease heterogeneity, and targeted therapy is still unavailable. Substantial evidence shows that RNA methylation plays a vital role in the mechanisms of the immune response, leading to speculation that it should also be related to the occurrence and development of SLE. RNA methylation has been a hot topic in the field of epigenetics in recent years. In addition to revealing the modification process, relevant studies have tried to explore the relationship of RNA methylation with the occurrence and development of various diseases. At present, some studies have provided evidence of a relationship between RNA methylation and SLE pathogenesis, but there is a lack of in-depth research and analysis. This review will start with the specific mechanism of RNA methylation and its relationship with the immune response to propose an association between RNA methylation and SLE pathogenesis based on existing studies and then discuss the future direction of this research.